2010
DOI: 10.1111/j.1399-0012.2010.01368.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive familial intrahepatic cholestasis: a single‐center experience of living‐donor liver transplantation during two decades in Japan

Abstract: The clinical courses and outcomes of PFIC1 recipients after LDLT are still not sufficient owing to steatosis/fibrosis, unlike the case for PFIC2 recipients. As PFIC1 patients will require LT during the long-term progression of the disease, further strategy improvements are required for PFIC1 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 40 publications
7
56
0
Order By: Relevance
“… Hori et al74 and Miyagawa‐Hayashino et al75 reported the same cohort of patients. Miyagawa‐Hayashino et al reported only the 8 PFIC1 patients with steatosis.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“… Hori et al74 and Miyagawa‐Hayashino et al75 reported the same cohort of patients. Miyagawa‐Hayashino et al reported only the 8 PFIC1 patients with steatosis.…”
Section: Resultsmentioning
confidence: 87%
“…Posttransplant NAFLD in pediatric liver transplant recipients has been documented only in case series and reports69‐77 (Table 5). Four of the 19 children reported in these studies underwent transplantation for cirrhosis associated with nonalcoholic steatohepatitis (NASH) 69‐71.…”
Section: Resultsmentioning
confidence: 99%
“…However, after restoration of bile flow, i.e. after LTx, high concentrations of bile salts enter the lumen of the intestine, which in combination with bile salt malabsorption may result in spillover of bile salts to the colon and in exacerbation of diarrhea that can be ameliorated by application of bile salt-binding resins [15][16][17][18][19]. This favors the hypothesis that intestinal bile salt malabsorption may be the underlying cause of diarrhea.…”
Section: Discussionmentioning
confidence: 75%
“…Extrahepatic symptoms such as diarrhea and hearing loss are common in PFIC1 and BRIC1 patients [10,13,14]. After LTx, PFIC1 patients have a high risk (~85%) of developing an exacerbated form of diarrhea, possibly as a consequence of restored bile flow [15][16][17][18][19]. Diarrhea is ameliorated upon treatment with bile salt-absorptive resins such as cholesevelam and cholestyramine [20].…”
Section: Introductionmentioning
confidence: 97%
“…No effective medical therapy for this disease is currently available [3]. Even liver transplantation is insufficient to improve the clinical course and outcomes of patients with PFIC1 because of steatosis and fibrosis [4]. …”
Section: Introductionmentioning
confidence: 99%